NF-κB inhibition in dendritic cells pre-treated with sulforaphane-conjugates induces immunotolerance - Leiva-Castro, Camila; Múnera-Rodríguez, Ana M.; Martínez-Bailén, Macarena; Carmona, Ana T.; López-Enríquez, Soledad; Palomares, Francisca (bioRxiv, 2024)
Sulforaphane (SFN) has notable health benefits but faces challenges due to poor solubility and delivery. This study explores SFN glycoconjugates’ effects on LPS-induced inflammation in human dendritic cells (DCs), aiming to enhance therapeutic potential against inflammatory diseases. Monovalent SFN-glycoconjugates with mannose (SFNMan) and fucose (SFNFuc) were developed and tested for their anti-inflammatory and immune-modulatory properties in DCs from healthy donors under chronic LPS exposure. Our results revealed that carbohydrate-functionalized SFN improves solubility and effectiveness in suppressing inflammation by targeting the p65 NF-κB pathway, without affecting MAPK signaling. SFN-glycoconjugates induce a tolerogenic immune response, characterized by increased IL-10 production and enhanced regulatory T- and B-cell proliferation. Notably, these effects surpass those of p65 NF-κB inhibition alone, highlighting a distinct and potent regulatory mechanism independent of MAPK pathways. These findings demonstrate the promise of SFN-glycoconjugates as innovative therapeutic agents for inflammatory diseases, offering enhanced anti-inflammatory and immunomodulatory effects through improved delivery and targeted molecular pathways.